RISK MANAGEMENT AND PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN OSUN STATE, NIGERIA - Afolabi, Taofeek Sola; James, Joseph Tugudu (Archives of Business Research, 2018)
Abstract Small and Medium Enterprises (SMEs) in both developing and developed economies play crucial roles in economic development through wealth creation, employment opportunities and poverty alleviation. However, the uncertainties surrounding businesses require SMEs to effectively manage their risk exposures. This study examined the influence of risk management practices on the performance of SMEs in Osun state, south-western Nigeria. A total of 340 SME operators in the state were chosen for this study and primary data were collected through a structured questionnaire which was administered to managers/operators of the selected SMEs. A total of 330 copies of the questionnaire were returned having been correctly filled and deemed suitable for this research. A linear regression model, through the Ordinary Least Squares technique was used for the data analysis and test for hypothesis, with the aid of the E-view statistical software. The result from the analysis revealed a significant relationship between risk management and the performance of SMEs (t-value=23.47; p<0.05). The result further showed that attitude to risk positively affects risk management practices and that there is a strong positive correlation between risk identification and risk management (r=0.92). The study therefore concluded that risk management practices have significant and positive influence on the performance of SMEs in Osun state. It was recommended that SME operators in Nigeria should put in place cost-effective measures for timely risk identification and effective risk mitigation in order to ensure that their financial performance is not negatively impacted.